1996
DOI: 10.1152/jn.1996.75.2.931
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of neocortical neurons in slices from children with intractable epilepsy

Abstract: 1. The intrinsic electrical properties of human neocortical neurons were studied with current-clamp and single-electrode voltage-clamp techniques in slices obtained from children, aged 3 mo to 15 yr, undergoing surgical treatment of intractable epilepsy. Neocortical samples were classified as most or least abnormal based on clinical data. Recorded neurons were labeled with biocytin for correlation of electrical properties with morphological characteristics and laminar position. All recorded neurons were divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 11 publications
3
24
0
1
Order By: Relevance
“…Although the average frequencies reported here are not very high, we have to consider that firing rates were calculated at just above threshold and thus do not reflect the maximal frequency. At higher stimulation intensities some interneurons could reach frequencies greater than 100 Hz, consistent with human and animal studies (21,22). Some cytomegalic cells also showed decreased Na + spike inactivation.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Although the average frequencies reported here are not very high, we have to consider that firing rates were calculated at just above threshold and thus do not reflect the maximal frequency. At higher stimulation intensities some interneurons could reach frequencies greater than 100 Hz, consistent with human and animal studies (21,22). Some cytomegalic cells also showed decreased Na + spike inactivation.…”
Section: Discussionsupporting
confidence: 84%
“…Although these patterns can be very diverse (15), 3 general categories are accepted and include the fast-spiking, the low-threshold or burst spiking, and the regular-spiking interneurons. In a previous study using cortical slices from pediatric epilepsy patients, all interneurons were found to be fast-spiking (22). In our population, most normal-appearing and cytomegalic interneurons fired fast, repetitive action potentials with no or weak adaptation, either spontaneously or in response to depolarizing current injection and were considered fastspiking interneurons, which is consistent with their predominantly basket cell morphology.…”
Section: Electrophysiology Of Normal and Cytomegalic Interneuronssupporting
confidence: 74%
“…On the basis of previous in vitro studies (McCormick et al, 1985), we have focused our efforts on so called fast spiking (FS) cells that have at least three distinct intrinsic characteristics: very brief action potential duration, little or no spike frequency adaptation in response to Physiological Properties of Inhibitory Interneurons in Cat Striate Cortex intracellular depolarizing current injection, and a steep linear relationship between discharge frequency and amplitude of current injection. Cells having these properties have been shown to correlate well with the morphological characteristics of a subset of GABAergic interneurons, including basket cells and chandelier cells (McCormick et al, 1985;Naegele and Katz, 1990;Kawaguchi andKubota, 1993, 1997;Jones and BĂŒhl 1993;Tasker et al, 1996). Here we determine the intrinsic membrane properties, responses to visual stimuli, receptive field properties, and selectivity for stimulus orientation and direction of fast spiking interneurons in the cat primary visual cortex.…”
Section: Introductionmentioning
confidence: 91%
“…Consequently the study of neocortical inhibitory interneurons has been largely restricted to the in vitro slice preparation. These studies have revealed the intrinsic electrophysiological properties of these neurons as well as their important role in the regulation of neuronal excitability (McCormick et al, 1985;Jones and Heinemann, 1988;Foehring et al, 1991;LlinĂ s et al, 1991;Jones and BĂŒhl 1993;Kawaguchi, 1995;Chen et al, 1996a;Kawaguchi andKubota, 1996, 1997;Tasker et al, 1996;Thomson et al, 1996;Thomson and Deuchars, 1997). Although this technique has clear advantages for studying the cellular properties of interneurons, it has obvious limitations for investigating physiological function.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has become evident that L5 PT and IT neurons within rodent PFC possess distinct intrinsic properties, local connectivity, and long-range inputs. Although most of these differences have been characterized in rodents, different categories of PFC pyramidal neurons are also present in humans and non-human primates (Foehring et al, 1991; Tasker et al, 1996; Chang and Luebke, 2007). PT and IT neuron categories can be further subdivided into groups based on gene expression, specific projection targets and laminar distribution.…”
Section: Pfc Projection Neuronsmentioning
confidence: 99%